(untitled) (Ozone Therapy Global Journal, 2011)
A n ewer treatment, autologous p l a telet - r ich plas ma (PRP), r e presents a gre a ter sim i l arity to the n atura l healing process as a composite of multiple growt h f actors , is safe due to its autologous nature, and is produced as needed from patient blood. PPR is an concentration of platelets and growth factors, including transforming growth factor-beta (TGF-b), vascular endothelial growth factor (VEGF), and platelet derived growth facto r (PDGF). The enhancement of tis sue h e a ling by the placeme n t of supr aphysi o l o g ic conc e n tration of autologous p latel e ts at the site of tissue inj u r y or s u r g e r y i s su p p o r ted by bas i c science and c linical studies. Due to the increased concentration and release of these factors, PPR can potentially enhance the recruitment and proliferation of s tem cells and endothel i a l cell s. O zone can pr o mote platelet aggrega tio n a n d release of grow f a ctors wi th both m it o g enic and c h e motac ti c proper tie s. In additio n t o us e in the t r eat ment o f chro n ic skin a nd sof t ti ssue ulcera ti o ns , a ppli ca ti o n of thi s method includ e per i odontal and o ral s u rgery, maxillofacial surgery, ortho pedic an d trauma surgery, cos metic and plastic surgery, spina l surgery, heart by pass surgery, and burns. A bette r understanding of pla telet function and appropriate clinical use is essential in achieving the desired outcomes of platelet-rich concentrate in clinical applications.